2021
DOI: 10.1177/09544054211040633
|View full text |Cite
|
Sign up to set email alerts
|

Contribution to the selection of cutting fluid type and its application technique for grinding of bearing steel

Abstract: The elevated heat generation in grinding can develop high temperatures at the contact zone, which can adversely affect the surface integrity of the workpiece, especially when grinding hardened steels with conventional abrasives. Thus, the correct selection of cooling-lubrication condition is essential to avoid or attenuate any possible negative effect to workpiece surface integrity. However, the literature lacks work comparing different cutting fluid application technique (e.g. flood and minimum quantity lubri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…54,55 The most effective way to preserve the optimal range of cutting temperatures is using cutting fluids since their functions allow for cooling/lubricating the cutting zone. 56 Conventional wet machining or flooding may be incapable to reach the critical areas constantly mostly due to chip movements. Moreover, the negative impacts of this method on environment and human health, popularity of wet machining lessens day-by-day owing to eco-benign concerns.…”
Section: Evaluation Of Cooling and Lubricating Mechanisms And Cutting...mentioning
confidence: 99%
“…54,55 The most effective way to preserve the optimal range of cutting temperatures is using cutting fluids since their functions allow for cooling/lubricating the cutting zone. 56 Conventional wet machining or flooding may be incapable to reach the critical areas constantly mostly due to chip movements. Moreover, the negative impacts of this method on environment and human health, popularity of wet machining lessens day-by-day owing to eco-benign concerns.…”
Section: Evaluation Of Cooling and Lubricating Mechanisms And Cutting...mentioning
confidence: 99%
“…Schwendemann et al [ 26 ] discussed the most important methods for fault analysis of grinder bearings and introduced the prediction of remaining service life. Paiva et al [ 27 ] analyzed the morphology of the ground surface and the microhardness below the machined surface. The results showed that the surfaces milled with semi-synthetic fluid usually had lower Ra values and microhardness changes.…”
Section: Introductionmentioning
confidence: 99%
“…For better machining performance, the cutting fluids are applied at the interface area to absorb the maximum heat energy, and the rest heat is transferred to the workpiece and abrasive wheel. 8 Their main functions are cooling and lubrication. As a consequence of the wide contact region between the abrasive wheel and the workpiece, coolant supply is challenging during the grinding operation, resulting in thermal damage to the workpiece surface.…”
Section: Introductionmentioning
confidence: 99%